A new portable sampler of atmospheric methane for radiocarbon measurements - G. Zazzeri; G. Zazzeri; L. Wacker; N. Haghipour; P. Gautschi; T. Laemmel; T. Laemmel; S. Szidat; S. Szidat; H. Graven (Atmospheric Measurement Techniques)
Radiocarbon (14C) is an optimal tracer of methane emissions, as 14C measurements enable distinguishing between fossil methane and biogenic methane (CH4). However, 14C measurements in atmospheric methane are still rare, mainly because of the technical challenge of collecting enough carbon for 14C analysis from ambient air samples. In this study, we address this challenge by advancing the system in Zazzeri et al. (2021) into a much more compact and portable sampler and by coupling the sampler with the MICADAS (MIni CArbon DAting System) accelerator mass spectrometry (AMS) system at ETH Zurich, using a gas interface.